Prevalence of Subdural and Epidural Hematoma in Head Trauma Patients: A Cross-sectional Study - Reza Morovatshoar; Seyed Ashkan Tabibzadeh Dezfouli; Saeed Hosseini Teshnizi; MohammadHosein Sheybani-Arani; Fatemeh Khajavi-Mayvan; Ali Salimi Asl; Maryam Sahafibandary; Reza Yazdani (Disease and Diagnosis, 2024)
Background: Epidural hematoma (EDH) and subdural hematoma (SDH) are common complications after traumatic brain injury. Intracranial hematomas can be without complications or associated with life-threatening conditions, including midline shift, cerebral edema, intracerebral ischemia, and increased intracranial pressure. This study aimed to investigate the prevalence of EDH and SDH in patients with head trauma attending the emergency department. Materials and Methods: This descriptive cross-sectional study included 146 patients with head trauma referred to the Emergency Department of Shahid Mohammadi Hospital, Bandar Abbas, in 2021. Patients’ data, including age, gender, Glasgow Coma Scale (GCS) on admission, mechanism of trauma, type of hematoma, length of intensive care unit (ICU) stay, outcome (recovery/death), and neurosurgery requirements were extracted from their medical files. Results: The mean age of the participants was 20.97±15.05 years, of whom 114 (78.1%) were male. EDH and SDH were observed in 7.5% and 11% of patients, respectively. The most common mechanism of trauma was traffic accidents (39%), followed by falls (28.1%) and assaults (13%). Moreover, 11% of the patients needed neurosurgical intervention. Most patients recovered (95.9%), and 4.1% died. The mean GCS on admission was 13.47±2.34. Furthermore, SDH was significantly higher in the patients who died (P=0.001) and those aged≥18 years (P=0.028). Conclusion: The results of the current study showed a higher prevalence of SDH compared to that of EDH. Both hematoma types appeared to correlate with the mechanism of trauma, ICU admission, GCS on admission, and neurosurgery requirement, while SDH was associated with age and death.